2014
DOI: 10.1002/pd.4469
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of fetal respiratory function: evaluation of fetal lung maturity using lung‐to‐liver signal intensity ratio at magnetic resonance imaging

Abstract: ObjectiveThe purpose of this retrospective study is to determine the fetal lung-to-liver signal intensity ratio (LLSIR) on T2-weighted images for the prediction of neonatal respiratory outcome.MethodsOne hundred ten fetuses who underwent magnetic resonance imaging (MRI) examination for various indications after 22 weeks of gestation participated in this study. LLSIR was measured as the ratio of signal intensities of the fetal lung and liver on T2-weighted images at MRI. We examined the changes of the ratio wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 22 publications
(48 reference statements)
0
24
0
2
Order By: Relevance
“…We hypothesized that when ipsilateral lung was not detected at the apex, contralateral lung maturity provided important prognostic information. We selected LLSIR values greater than 2.0 as indicative of maturity (11) validated this as predictive of outcome, suggesting that this value reflects contralateral lung maturation. When values were less than 2.0, contralateral lung maturation was insufficient to support survival (Grade III), whereas contralateral lung maturation was more likely to allow survival (Grade II), although with a requirement for intensive management using iNO or ECMO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that when ipsilateral lung was not detected at the apex, contralateral lung maturity provided important prognostic information. We selected LLSIR values greater than 2.0 as indicative of maturity (11) validated this as predictive of outcome, suggesting that this value reflects contralateral lung maturation. When values were less than 2.0, contralateral lung maturation was insufficient to support survival (Grade III), whereas contralateral lung maturation was more likely to allow survival (Grade II), although with a requirement for intensive management using iNO or ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…Stratification was performed utilizing coronal sections of T2-weighted MRI studies obtained after 29 weeks of gestation. LLSIR was calculated by the study radiologist (Y Sugioka) as reported by Oka et al (11). We placed one region of interest (ROI) within the homogenous portion of the liver and the contralateral lung on the same section.…”
Section: The Stratification Algorithmmentioning
confidence: 99%
“…The SSFSE sequence technique also allows clear visualization of the aortic arch anatomy. To account for effects of fetal movement, we repeated sequences that were degraded by fetal motion [6] . Fetal MRI may also provide relevant information on lung volume and signal intensity, and is an accurate prenatal method for evaluating fetal lung maturity using the lung-to-liver signal intensity ratio on T2-weighted images [5] .…”
Section: Discussionmentioning
confidence: 99%
“…Low lung signal intensity is considered to reflect a low lung fluid volume, which is associated with pulmonary hypoplasia. 6,8,9 Although LLSIR positively correlated with gestational age, normalization according to gestational age was not performed in these studies. 6,8,9 In the present study, we constructed the reference range of LLSIR for normal fetuses and retrospectively assessed the use of LLSIR to predict functional pulmonary hypoplasia (FPH) with respect to gestational age.…”
Section: Introductionmentioning
confidence: 89%